Twist-and-turn spin squeezing in Bose-Einstein condensates - Müssel, Wolfgang; Strobel, Helmut; Linnemann, Daniel; Zibold, Tilman; Oberthaler, Markus K. (Physical review. A, Atomic, molecular, and optical physics, 2015)
We demonstrate experimentally an alternative method for the dynamic generation of atomic spin squeezing, building on the interplay between linear coupling and nonlinear phase evolution. Since the resulting quantum dynamics can be seen as rotation and shear on the generalized Bloch sphere, we call this scheme twist-and-turn. This is closely connected to an underlying instability in the classical limit of this system. The short-time evolution of the quantum state is governed by a fast initial spreading of the quantum uncertainty in one direction, accompanied by squeezing in the orthogonal axis. We find an optimal value of ξ2S=−7.1(3) dB in a single Bose-Einstein condensate and scalability of the squeezing to more than 104 particles with ξ2S=−2.8(4) dB.